Bondage : human rights & development - Mishra, Lakshmidhar (New Delhi Vitasta Publishing, 2020)
ost Indian states and UTs are in denial mode about the existence of bonded labour. Law Enforcers have mostly not lived up to the laudable intentions of the frameworks of the bonded labour (abolition) Act, 1976. Governments failed to translate into action the directions of the Supreme Court and recommendations of the National human rights Commission. This book seeks to change the mind-set of those tasked with removing modern-day bondage. It seeks to promote a broad awareness and critical consciousness about the provisions of the Constitution in the minds of all stakeholders, especially Non-profits. This has been done through a dialectical exercise or Q&A format.
Keywords: IAS as an author; 1964 Batch; Human rights